Dual metal oxide loaded cotton/polyester fabric with photo, bio and magnetic properties. (August 2020) - Rastgoo, Madine; Montazer, Majid; Harifi, Tina; Mahmoudi Rad, Mahnaz
This research aimed at sonochemical synthesis and deposition of Fe3 O4 /ZnO nanocomposites on cotton/polyester fabric using the ultrasonic bath at 80℃. For this purpose, in situ sonosynthesis of magnetite nanoparticles on the fabric surface was carried out and followed by the generation of crystalline ZnO nanoparticles through the sonochemical approach, eliminating the need for high temperature after-treatment of the fabrics. This effect was achieved thanks to the shock waves formed by the cavitation bubbles also called microcalcination, resulting in the formation and adsorption of crystalline nanomaterials on the fabric surface. Magnetic properties with saturation magnetization of 1.5 emu/g, self-cleaning activities toward methylene blue discoloration, and excellent antibacterial and antifungal properties along with low cell toxicity were among the obtained properties. The current study is the first research indicating the potential of the sonochemical method to produce non-toxic cotton/polyester fabric with various properties including magnetic, photocatalytic, and antibacterial activities.